Solution thermodynamics and preferential solvation of 3-chloro-N-phenyl-phthalimide in acetone + methanol mixtures (2016)
The thermodynamic properties of the 3-chloro-N-phenyl-phthalimide in acetone + methanol cosolvent mixtures were obtained from solubility data report in literature. The solubility was higher in near acetone and lower in pure methanol at all temperatures studied. A non-linear plot of ∆solnH° vs. ∆solnG° shows a negative slope from pure acetone up to x1 = 0.691. Beyond this composition, a variable positive slope is obtained with the exception of mixtures with x1 = 0.121, x1 = 0.272 and x1 = 0.356 which is a not common trend in these systems. The preferential solvation of 3-chloro-N-phenyl-phthalimide by the components of the solvents was estimated by means of the inverse Kirkwood–Buff integral method, showing the 3-chloro-Nphenyl-phthalimide is preferential solvated by methanol in more polar mixtures and by acetone in less polar ones.